Active current sheets and candidate hot flow anomalies upstream of Mercury's bow shock. Issue 2 (10th February 2014) - Uritsky, V. M.; Slavin, J. A.; Boardsen, S. A.; Sundberg, T.; Raines, J. M.; Gershman, D. J.; Collinson, G.; Sibeck, D.; Khazanov, G. V.; Anderson, B. J.; Korth, H.
<x xml:space="preserve">Abstract</x> Hot flow anomalies (HFAs) represent a subset of solar wind discontinuities interacting with collisionless bow shocks. They are typically formed when the normal component of the motional (convective) electric field points toward the embedded current sheet on at least one of its sides. The core region of an HFA contains hot and highly deflected ion flows and rather low and turbulent magnetic field. In this paper, we report observations of possible HFA‐like events at Mercury identified over a course of two planetary years. Using data from the orbital phase of the MESSENGER mission, we identify a representative ensemble of active current sheets magnetically connected to Mercury's bow shock. We show that some of these events exhibit magnetic and particle signatures of HFAs similar to those observed at other planets, and present their key physical characteristics. Our analysis suggests that Mercury's bow shock does not only mediate the flow of supersonic solar wind plasma but also provides conditions for local particle acceleration and heating as predicted by previous numerical simulations. Together with earlier observations of HFA activity at Earth, Venus, Mars, and Saturn, our results confirm that hot flow anomalies could be a common property of planetary bow shocks and show that the characteristic size of these events is controlled by the bow shock standoff distance and/or local solar wind conditions.